No-minute Noodler: Dag's Dictionary for Kids - Glover, Richard (Sydney,New South Wales : HarperCollins Publishers, 2011)
No-minute noodler: a kid who eats the two-minute noodles straight from the packet without even cooking them! Dinobore: a kid who can t talk about anything other than dinosaurs. Bumboozle: to confuse the issue of who it was that farted by blaming it all on the dog! A very funny book of words that should exist but don't! Includes a great do-it-yourself section for kids at the back.
Imprint: ABC Books.
Keywords: Reference - Dictionaries; Dictionaries; Australian